Note on a work life (qualifying as a new sport for the Olympic Games): When performance management and contemporary work life are in perfect harmony - Kirkegaard, L. (ephemera. theory & politics in organization, 2018)
I often wonder whether contemporary work life could qualify as a distinct sports event for the Olympic Games? Once in a while, I catch a glimpse of indications that this might be the case. This note is an allegory of contemporary work life as an elite sport told by high profiled management consultants.